The Impact of Digital Wallet Use (Fintech Payment) on Students’ Personal Financial Management DANA Application Users - Neri Susanti; Kresnawati Kresnawati; Nabilla Dwi Sakina; Gita Rafika Rahma; Cemas Astiana; Suiska Minarti; Meta Riana; Evi Febriani (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the impact of digital wallet usage, specifically the DANA application, on the personal financial management of university students. Using a quantitative survey approach, data was collected from students who actively use DANA in their daily financial transactions. The findings indicate that the intensity of digital wallet usage significantly influences students' financial management, particularly in monitoring expenditures and accessing transaction histories. Promotional features such as cashback and discounts have also been proven to increase students' consumption behavior. The study further shows that digital financial literacy plays a crucial role in ensuring responsible use of digital payment tools. These results imply the need for enhanced financial literacy education in higher education institutions to support healthy financial behavior among young digital users.